Aktivisme Digital Warganet Muhammadiyah dalam Menyuarakan Isu Krisis Iklim dan Lingkungan Pada Tagar #Milad111Muhammadiyah - Sofia Hasna (Jurnal Riset Komunikasi (JURKOM), 2025)
In 2023, Indonesia faced a severe climate and environmental crisis. Issues such as the waste crisis, air pollution, and natural disasters called for social movements. Digital activism on social media emerged as a powerful tool to drive change. On its 111th anniversary, Muhammadiyah raised the theme "Ikhtiar Menyelamatkan Semesta", utilizing social media to raise awareness and encourage the public to care for the environment. The aim of this research is to analyze the social media network on X/Twitter through the hashtag #Milad111Muhammadiyah as a form of digital activism by Muhammadiyah netizens in voicing concerns over the climate and environmental crisis. This research uses a descriptive qualitative analysis of conversations related to the theme "Ikhtiar Menyelamatkan Semesta," focusing on social media data from X/Twitter during the period of November 16-22, 2023, with the keyword #Milad111Muhammadiyah. The research concept uses the theories of The Network Society and Opinion Leader. The results show a close-knit network pattern within the Social Media Network, which generated high enthusiasm and solidarity among netizens, especially in the Muhammadiyah cluster. This movement formed a large network of accounts from Muhammadiyah members, alternative media, Muhammadiyah's social enterprises, and Muhammadiyah's autonomous organizations. The Muhammadiyah anniversary was also marked by other popular hashtags, such as #Muhammadiyah (1149 tweets), #IkhtiarMenyelamatkanSemesta (796 tweets), and #MiladMuhammadiyah (465 tweets). This research highlights the strong solidarity of Muhammadiyah netizens through social media activism, particularly regarding the environmental and climate crisis, as well as the important role of opinion leaders in digital campaign movements.